Probing Galactic Black Holes with Microlensing with Gaia and OGLE. Issue Volume 14:Issue S339(2018) (November 2017) - Wyrzykowski, Ł.; Rybicki, K. A.; Kruszyńska, K.; Gromadzki, M.; Zieliski, P.; Kostrzewa-Rutkowska, Z.; Hodgkin, S. T.
Abstract: As shown by recent gravitational wave detections, galaxies harbour an unknown population of black holes at high masses. In our Galaxy such dark objects can be found and studied solely via gravitational microlensing methods. This paper described our search for black-hole lenses both in archived OGLE data and among on-going microlensing events found by OGLE and Gaia . That combination of superb time-domain astrometry and photometry will enable us to derive masses and distances to these dark lenses uniquely, and to describe the demographics of the unseen component of the Milky Way.